National program of upgrade 20,000 Small and medium-sized enterprises what's new ? - Abdellatif, Amira; Labou, Mohamed Lamine (Journal of Human Sciences, 2020)
This study aims to evaluate the national programme of upgrading 20,000 small and medium-sized enterprises in Algeria and to know what distinguishes it from other previous programs.So this study deals with the various upgrade programs adopted by Algeria and precisely the last program where all the capabilities are used to succeed.Finally, it is concluded in this study that the national upgrade program of 20,000 small and medium-sized enterprises, has not been able to achieve its objectives because of the slowness and complicated funding procedures, and the lack of experience at the level of the agency responsible for the upgrade operations.